Corporate ownership structure and performance: an Indian perspective. (2nd June 2021) - Tiwari, Ranjit; Kumar, Santosh
In this study, we examined whether there is any evidence to support the view that the variation in firms' promoter ownership structures and non-promoter ownership structures result in systematic differences in the observed firm performance in either direction within the context of the Indian capital market. 645 listed companies from the Bombay Stock Exchange for the period of 2008 to 2018 were considered for the sample. Further, the GMM model was used for estimation to account for potential endogeneity in the hypothesised relationship. Our results suggest that concentrated ownership negatively influences firm performance, whereas diffused ownership has a significant positive impact. This study is unique because we have measured the relationship of both concentrated and diffused ownership structure with firm performance in either direction, which is rare in the Indian context. We have also tried to understand which among the sub-components of concentrated and diffused ownership structure are the most essential driving forces of performance. We have also analysed this relationship across different industry groups, an aspect not often addressed in financial literature.